Sexism in Translation: A Study of Nobokov’s Lolita and Its Indonesian Translation - Nurochman, Nurochman; Wibowo, Agung Prasetyo (Makassar State University, 2024)
This research investigates kinds of sexist language and technique of translation from novel Lolita and its translation in Indonesia. The aims of the study are: (1) to analyze the kinds of sexist language in Vladimir Nabokov’s Lolita, (2) to analyze the techniques of translation that used to translate sexist expression in the novel Lolita. The study applied a descriptive qualitative method. In this case, the writer collected, classified, and described the data using the method. The source of data consists of documents taken from novel Lolita with its translation. To get the data, the writer read the English and the Indonesian novel carefully and identified the kinds of sexist language and its translations. The writer got 100 data of sexist language and 105 data for techniques of translation. The reason why the data of translation techniques are more than the data of characteristics of sexist language is because there is one data that used more than one translation techniques. The results of the study showed that: (1) there are 5 kinds of sexist language found in the novel i.e. 1) Man as Standard, 2) Women Are Different, 3) Non-Human Terms, 4) Negative Words, and the last, 5) Sex-Role Descriptors, (2) there are 8 kinds of translation technique used to translate sexist expression i.e. adaptation, borrowing, established equivalent, generalization, description, modulation, variation, and deletion.